Association between periodontal disease and prostate disease: a mini review - Li, Shuxin; Cao, Hongliang; Zhang, Yueqiu; Yang, Tong; Li, Mingxuan; Lv, Chensen; Lian, Xin (Frontiers in Cellular and Infection Microbiology, 2025)
Periodontal disease (PD) is one of the most common chronic diseases in the oral cavity, typically referring to chronic inflammation caused by infection with pathogenic microorganisms in the oral cavity. PD primarily affects the tissues surrounding the teeth, leading to inflammation of the gums and periodontal tissues, destruction of the alveolar bone, and even loosening of the teeth. Numerous studies have shown that PD is not limited to the oral cavity but is also associated with the occurrence of diseases in multiple systems throughout the body. In recent years, increasing attention has been directed toward the interaction between PD and prostate diseases. This article reviews the potential associations between PD and prostate conditions such as chronic prostatitis, benign prostatic hyperplasia (BPH), and prostate cancer (PCa). It explores the pathological mechanisms underlying this interaction and its clinical implications. Additionally, this article aims to identify potential pathogenic mechanisms and propose possible approaches for preventing and treating prostate diseases through the management of PD.